Depression symptoms level among thyroid disorders patients at central region of Peninsular Malaysia - Jaafaf, Siti Nur Illani; Daud, Azlina; Saidi, Sanisah; Musa, Ramli; Nik Ahmad, Nik Nur Fatnoon (Malaysian Psychiatric, 2017)
Background of Study: Patients with thyroid disorders were found to have continued to experience symptoms of depression despite the great of treatment has been given to the patient to balance the thyroid hormones. Objective: The aim of this study is to determine the level of depression symptoms among various types of thyroid disorders patients. Methods: A cross sectional study was carried out at one of the government hospital at central region of Peninsular Malaysia from August to October 2016. Patients were diagnosed as thyroid disorders, Malaysian citizen, above 18 years old and did not have any psychiatric disorders were included in this study.Depression Anxiety Stress Scale-42 (DASS-42) was selected to determine the severity of depression symptoms and interpreted as follow: less than 9-no depression, between 10 and 13-mild depression, between 14-20-moderate depression, between 21 and 27- severe depression and more than 28-extreme severe depression. Descriptive statistic was analysed by IBM Statistical Package for the Social Sciences (SPSS) version 21.0. Results: About 15% (23) out of 153 thyroid patients had varies degree of depression symptoms from mild to severe extremely depression. Patients who had hyperthyroid were found to have more depressed, followed by hypothyroid and thyroid cancer group. Conclusion: These findings would suggest that the depression score was higher in the patients who have hyperthyroid. A more detail and thorough study is recommended to be done, in order to confirm these findings.